(untitled) - Ede, Lisa (New York, 1992)
This book contains full discussion of the concept of the rhetorical situation, explicit support for and reinforcement of collaborative learning and writing activities,..
Keywords: English language,English language,Anh ngữ thực hành,Anh ngữ thực hành; Rhetoric,Writing,Tu từ học,Viết